Molecular insight into amyloid oligomer destabilizing mechanism of flavonoid derivative 2-(4′ benzyloxyphenyl)-3-hydroxy-chromen-4-one through docking and molecular dynamics simulations. Issue 6 (2nd June 2016) - Kumar, Akhil; Srivastava, Swati; Tripathi, Shubhandra; Singh, Sandeep Kumar; Srikrishna, Saripella; Sharma, Ashok
Abstract : Aggregation of amyloid peptide (Aβ) has been shown to be directly related to progression of Alzheimer's disease (AD). Aβ is neurotoxic and its deposition and aggregation ultimately lead to cell death. In our previous work, we reported flavonoid derivative (compound 1) showing promising result in transgenic AD model of Drosophila. Compound 1 showed prevention of Aβ-induced neurotoxicity and neuroprotective efficacy in Drosophila system. However, mechanism of action of compound 1 and its effect on the amyloid is not known. We therefore performed molecular docking and atomistic, explicit-solvent molecular dynamics simulations to investigate the process of Aβ interaction, inhibition, and destabilizing mechanism. Results showed different preferred binding sites of compound 1 and good affinity toward the target. Through the course of 35 ns molecular dynamics simulation, conformations_5 of compound 1 intercalates into the hydrophobic core near the salt bridge and showed major structural changes as compared to other conformations. Compound 1 showed interference with the salt bridge and thus reducing the inter strand hydrogen bound network. This minimizes the side chain interaction between the chains A–B leading to disorder in oligomer. Contact map analysis of amino acid residues between chains A and B also showed lesser interaction with adjacent amino acids in the presence of compound 1 (conformations_5). The study provides an insight into how compound 1 interferes and disorders the Aβ peptide. These findings will further help to design better inhibitors for aggregation of the amyloid oligomer.